2009
DOI: 10.1128/jcm.01591-08
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Reduced-Cost Modified Selective Medium for Isolation of Clostridium difficile

Abstract: Both for epidemiologic studies and for diagnostic testing, there is a need for effective, economical, and readily available selective media for the culture of Clostridium difficile. We have developed a reduced-cost substitute for cycloserine-cefoxitin-fructose agar (CCFA), which is an effective but expensive selective medium for C. difficile. The modified medium, called C. difficile brucella agar (CDBA), includes an enriched brucella base as a substitute for proteose peptone no. 2, and the concentration of sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 20 publications
0
72
3
Order By: Relevance
“…It was noted whether the swabs had evidence of fecal staining, but all swabs were processed. The swabs were transferred to a Whitley MG1000 anaerobic workstation (Microbiology International, Frederick, MD) and cultured for C. difficile on prereduced cycloserine-cefoxitin-brucella agar containing 0.1% taurocholic acid and lysozyme at 5 mg/ml (CDBA) as previously described (10). The number of colonies was counted.…”
mentioning
confidence: 99%
“…It was noted whether the swabs had evidence of fecal staining, but all swabs were processed. The swabs were transferred to a Whitley MG1000 anaerobic workstation (Microbiology International, Frederick, MD) and cultured for C. difficile on prereduced cycloserine-cefoxitin-brucella agar containing 0.1% taurocholic acid and lysozyme at 5 mg/ml (CDBA) as previously described (10). The number of colonies was counted.…”
mentioning
confidence: 99%
“…Equal volumes of stool specimen and absolute ethanol were mixed and incubated at room temperature for 30 min. The alcohol-treated stool specimen was inoculated onto anaerobically reduced cycloserine-cefoxitin fructose agar (CCFA), and it was anaerobically incubated at 37ºC in an anaerobic jar for 48 to 72 h [9]. All bacteria used in this study were identified by odor and colony morphology on CCFA and cell morphology after Gram staining.…”
Section: Methodsmentioning
confidence: 99%
“…After 10 minutes of contact time, 1 mL of Dey-Engley neutralizer (Remel) was added, and viable organisms were quantified by plating on media selective for each pathogen. 10 Although the complete experiments included only a 10-minute contact time, preliminary experiments with the 3 C. difficile strains did demonstrate equivalent kiUing of spores at 5 and 10 minutes for both bleach and Sterilox HG, respectively. The experiments were repeated 3 times.…”
Section: Effectiveness Of An Electrochemicauy Activated Saline Solutimentioning
confidence: 99%
“…C. difficile spores were prepared as previously described. 10 Ten-microliter aliquots containing ~6 log 10 colony-forming units (CFUs) of the organisms suspended in deionized water with or without simulated organic load containing bovine serum albumin, tryptone, and mucin (0.5 : 5 :0.4% w/v) were spread to cover 1-cm-diameter polystyrene ceU culture wells (nest ceU culture plate, Denville Scientific). After the suspensions air dried, 300 IxL of deionized water, Sterilox HG, or 10% household bleach (Clorox) was added.…”
Section: Effectiveness Of An Electrochemicauy Activated Saline Solutimentioning
confidence: 99%
See 1 more Smart Citation